Punitive damages in private international law : lessons for the European Union / Cedric Vanleenhove - Vanleenhove, Cedric (Intersentia, 2016)
Although European scholars have called U.S. punitive damages an "(undesired) peculiarity of American law" and the "Trojan horse of the Americanisation of continental law", the European Union cannot close its eyes to this important feature of U.S. law. Despite being under constant scrutiny, punitive damages have a strong foothold on the other side of the ocean. Moreover, due to increased globalisation, transnational litigation is arguably on the rise. In cross-border law suits, it is inevitable that a jurisdiction will encounter legal institutions that are alien to the substantive law of the forum.This book examines the private international law treatment of American punitive damages in the European Union. It poses the crucial question whether U.S. punitive damages (should) penetrate the borders of the European Union through the backdoor of private international law. More specifically, three areas of private international law are analysed: service of process, applicable law and enforcement of judgments.In addition to describing the current positions in case law and scholarship, the book takes a normative perspective and attempts to formulate concrete guiding principles that can be used when the European legal order faces U.S. punitive damages. It, therefore, provides an invaluable resource for practitioners, judges and authorities confronted with this controversial remedy. Furthermore, as a nation's private international law attitude indicates the country's level of tolerance towards a foreign concept unknown in its own legal system, the book can form an essential building block for discussions amongst legislators surrounding the introduction of the remedy of punitive damages in substantive law.